2022
DOI: 10.3390/agronomy12112600
|View full text |Cite
|
Sign up to set email alerts
|

The Quality and Productivity of Strawberry (Fragaria × ananassa Duch.) Improved by the Inoculation of PGPR Bacillus velezensis BS89 in Field Experiments

Abstract: Efficient plant-growth-promoting rhizobacteria (PGPR) used as biofertilizers and biological control agents are promising substitutes for minimizing the application of synthetic agrochemicals in crop production. We studied the effect of PGPR strain Bacillus velezensis BS89 alone and in combination with three forms of nitrogen fertilizers (ammonium nitrate, carbamide, and ammonium sulfate) on the productivity of two strawberry varieties in three-year field experiments. We first showed that the application of PGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Halophytic plants are the best model for the isolation of bacterial endophytes helping with the elimination of excess salt concentrations [ 43 , 44 , 45 , 46 , 47 ]. Many bacteria of the genus Bacillus are able to stimulate plant growth and provide protection under biotic and abiotic stresses [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halophytic plants are the best model for the isolation of bacterial endophytes helping with the elimination of excess salt concentrations [ 43 , 44 , 45 , 46 , 47 ]. Many bacteria of the genus Bacillus are able to stimulate plant growth and provide protection under biotic and abiotic stresses [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus safensis TS3 was cultured in liquid potato-dextrose broth (PDB, Sigma, St. Louis, MO, USA) for 4 days at 28 °C in 500 mL flasks placed in a rotary shaker (180 rpm). The concentrations of indole 3-acetic acid (IAA), trans-Zeatin (tZ), and abscisic acid (ABA) in the bacterial suspension were determined using high-performance liquid chromatography (Agilent 1200, Santa Clara, CA, USA) with a mass-selective detector Varian 920-LC system as described in [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The content of chlorophyll a and b in quinoa seedlings inoculated with 11B91 was higher than that of quinoa seedlings inoculated with the LB blank control group at the first and third weeks, showing a trend of decreasing first and then increasing. This statement can be supported by Chebotar et al (2022) who showed that the inoculation of PGPR Bacillus velezensis BS89 led to an increase in the chlorophyll content of strawberry plants compared to the uninoculated control.…”
Section: Discussionmentioning
confidence: 83%
“…We compared our results with the effect of strain Bacillus velezensis BS89 on the productivity of two strawberry varieties (Fragaria × ananassa Duch.) [15], which demonstrated that BS89 produced a large amount of indole-3-acetic acid (IAA) (about 494.1 mg/mL). These data put forward an idea that in the strain consortiums, which we identified in our study, the high IAA-producing strain BS89 is also responsible for the improved root architecture and increased root formation of ryegrass.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of various crops (potatoes, spring and winter wheat, barley, sunflower, cabbage, carrots, and strawberry) with B. velezensis BS89 increased the yield from 12 to 40% [15,16].…”
Section: Microorganism Culturesmentioning
confidence: 99%